(untitled) (Journal of the College of Languages (JCL), 2014)
Writing as a female playwright in theatre gives a deeper depiction of woman’s real- self. Beth Henley has succeeded in providing a new realist vision of women’s abilities to face their inevitable tragic fates and how to conquer their despair. In Crimes of the Heart, the playwright uses certain method to present the development of the heroines’ characters through blending the tragic events with a comic frame. In fact, Henley focuses on the simple humorous activities more that the importance of the tragic event to present her vision of how to survive and face the crisis of life. Crimes of the Heart is a play that is concerned about three sisters whose lives are headed in distinctly different directions; however, they are struggling to get on their lives.